Structure, multiplexity, and centrality in a corruption network: the Czech Rath affair - Diviák, Tomáš (Trends in organized crime)
The present study is an analysis of a Czech political corruption network known as the Rath affair reconstructed with publicly available data. We argue that for the study of criminal networks it is fruitful to follow a multiplex approach, i.e., to distinguish several interdependent network dimensions and study how they are interrelated. Relational elements in corruption are identified, and we propose three dimensions that are essential for understanding the Rath network: pre-existing ties (e.g., marriage or co-membership of the same party), resource transfer (e.g., bribing), and collaboration (e.g., communication). The aim of the study was threefold. We aimed to examine if the network exhibits the core/periphery structure, to investigate the multiplex structure of the network by assessing the overlap of the main dimensions of the network, and to determine the central and multiplex actors while considering the differentiation of centrality according to the three network dimensions. The core/periphery model appears to have a perfect fit to the aggregated network, leading to a four-block adjacency matrix. Studying the frequency of ties in these blocks shows that collaboration ties are present in all the blocks, while resource transfer ties are mainly located between the core and periphery, and pre-existing ties are rare generally. We also identify central actors, none of which are strategically positioned, occupying more visible positions instead. The majority of actors display strong multiplexity in the composition of their own ties. In the conclusion the potential usefulness of multiplex descriptive measures and of mixed methods approaches, implications of our results for trust incriminal networks, and potential merits of analytical sociology approach are discussed.